The Effects of Worry and Relaxation on Flexibility During Cognitive Restructuring. Issue 6 (November 2018) - Stevens, Elizabeth S.; Jendrusina, Alexander A.; Legrand, Alison C.; Nahin, Erica R.; Kaufman, Michelle Goldwin; Borkovec, Thomas D.; Behar, Evelyn
Worry is associated with inflexibility in cognitive, emotional, and physiological functioning. In addition, worry's negative valence and abstract level of construal are rigid characteristics that contribute to its nonadaptive consequences. Relaxation and cognitive therapy aim to increase flexibility in chronic worriers, and may have greater efficacy when administered in combination. We examined the extent to which relaxation enhances and/or worry inhibits cognitive flexibility during a cognitive restructuring exercise in which participants generated alternative predictions for their worries. Participants ( n = 189) were randomly assigned to engage in relaxation, worry, or neutral thinking prior to cognitive restructuring. We measured the number and perceived likelihood of alternative predictions generated by participants, and coded those alternative predictions for their degree of positive valence, negative valence, and level of construal (abstractness to concreteness). Worry and relaxation did not lead to different numbers or perceived likelihood of alternative predictions. However, compared with participants with minimal symptoms of generalized anxiety disorder (GAD), those with elevated symptoms of GAD who engaged in prior worry generated alternative predictions characterized by greater negative valence and more abstractness (i.e., less concreteness). We also found that greater negative valence of alternative predictions was associated with more abstractness, whereas greater positive valence of alternative predictions was associated with more concreteness. These findings suggest that after engaging in worry, individuals with GAD may be less able to flexibly shift from the use of nonadaptive characteristics (negative valence, abstractness) associated with feared outcomes to the use of more adaptive characteristics (positive valence, concreteness) when considering alternative predictions.